Acute renal failure: strategies for the management and treatments - JASJOT SINGH; ANNIE JOHN; MOHAMMAD SHAFI BHAT; DR. EKTA CHITKARA (International Journal of Pharma and Bio Sciences, 2017)
Acute renal failure (ARF) recently known as Acute Kidney Injury(AKI), characterized by sudden loss of ability of the kidney to excrete waste, concentrate urine, conserve electrolyte, and maintain fluid balance is a common condition. There is a rapid decline in glomerular filtration rate (GFR) and is usually marked by rapid rise in serum creatinine level. In sudden acute renal failure no biochemical changes occur and the only sign of ARF is low urine output. Azotemia is also a characteristic feature of ARF. Management includes correction of fluid and electrolyte levels; avoidance of nephrotoxin and kidney replacement therapy, when appropriate. The purpose of this review is to discuss the differential and possible treatments of acute renal failure. It also includes the discussion about possible etiologies, biochemical changes and recovery pattern of the patients.